Heterogeneous preferences of green vehicles by vehicle size: Analysis of Seoul case - Hahn, Jin Seok; Lee, Jang Ho; Choi, Keechoo (International Journal of Sustainable Transportation, 2018)
Although there are several policies for promoting green vehicles, green vehicles have yet to penetrate the market to the extent desired. To attain the goal, a complete understanding of consumers’ preferences of green vehicles is essential. This paper proposes and specifies the fuel-type choice models among conventional gasoline vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and electric vehicles by vehicle size using the stated preferences data collected in Seoul, Korea. The results highlight the need to accommodate the correlation between similar alternatives and the unobserved heterogeneity within the context of choosing a green vehicle. The choice probabilities of green vehicles are affected by the relative impacts of the vehicles’ attributes and socio-demographic variables, and both of these variables are affected by the sizes of the vehicles. For compact size and mid-size vehicles, the effects of operating costs were less than those of purchase prices; however, for the subcompact vehicles, the effects of operating cost were greater than those of purchase price. The parameter of operating costs was not statistically significant in the full-size model. With respect to electric vehicles, the availability of fuel stations would be more important in Seoul than in the U.S. These results can also be useful for policy makers in that they provide information about the impact of green vehicles’ attributes on the choice probabilities of green vehicles.
Keywords: Conventional gasoline; Mixed logit; Nested logit; Plug in hybrid electric vehicles; Socio-demographic variables; Stated preferences; Unobserved heterogeneity; Vehicle size; Green vehicle; mixed logit; nested logit; stated preference; vehicle size